(untitled) (Asian Journal of Agriculture, 2017)
Abstract. Faizal I, Emdi A. 2017. Analysis of flowering gene in palm oil (Elaeis guineensis). Asian J Agric 1: 53-58. Palm oil has always been an important commodity in Indonesia. The most common species of palm oil is Elaeis guineensis. Palm oil is a monoecious plant with a tendency to be a temporal dioecious. The female flower will be the one that produces palm oil fruit, which later is treated with palm oil while the male flower only takes part in the fertilization process. To know the ratio between female and male flower trees in a plantation, this study was performed to detect a distinction between female and male flowering gene sequences from DNA samples of E. guineensis. Based on a previous study that managed to characterize MADS-box gene of palm oil, a primer was designed and named GmG (Globosa-male-Gaps). The result shows that the primer can differentiate DNA sequence female and male flower of E.guineensis, Palm oil. However, further studies with full sequence and more samples are needed to find distinctive results between female and male flower sequences as the GmG primer could be used to design a specific marker or primer to detect the presence of female or male flower within a tree.